Dashboard for Electric Vehicles Using Design Thinking Methods with Human Machine Interface (HMI) Integration in the Battery Management System (BMS) - Perdana Suteja Putra; Siti Yuki Lestari; Silvi Istiqomah (JUMANTARA: Jurnal Manajemen dan Teknologi Rekayasa, 2026)
Transportation technology continues to evolve to support environmentally friendly energy use, with battery-powered electric vehicles (EVs) becoming one of the most widely adopted innovations. The Battery Management System (BMS) plays a crucial role in monitoring battery conditions. The design of an informative and user-centered dashboard becomes essential. This study presents the development of an informative EV dashboard by integrating HMI with BMS using the Design Thinking methodology. User needs were identified through Focus Group Discussion (FGD) and mapped using an empathy map, revealing essential information requirements such as State of Charge (SoC), State of Health (SoH), estimated range, navigation, and a simple, intuitive visual display. The ideation stage with the innovation canvas produced relevant feature concepts. The prototype was evaluated using the System Usability Scale (SUS) involving 20 respondents, resulting in an average score of 76.25, categorized as “Good” and acceptable. The findings indicate that the dashboard is easy to use and helps drivers better understand vehicle conditions. Overall, this research demonstrates that Design Thinking is effective in developing user-friendly dashboards that integrate HMI with BMS, thereby enhancing EV usability and supporting the acceleration of EV adoption in Indonesia.